2021
DOI: 10.1021/acsami.0c21584
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Broad-Band-Absorbed Thermoplasmonic 1D Nanochains for Smart Windows with Adaptive Solar Modulation

Abstract: Controlling solar transmission through windows promises to reduce building energy consumption. A new smart window for adaptive solar modulation is presented in this work proposing the combination of the photothermal one-dimensional (1D) Au nanochains and thermochromic hydrogel. In this adaptive solar modulation system, the Au nanochains act as photoresponsive nanoheaters to stimulate the optical switching of the thermochromic hydrogel. By carefully adjusting the electrostatic interactions between nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…T lum (380–780 nm), T solar (300–2500 nm) and D T solar could be determined by the following equations: Tlum,solar= ϕlum,solarλTλdλϕlum,solarλdλ ΔTlum,solar=Tlum,solarTTlum,solar20 normalC where ϕ lum (λ) is the standard luminous efficiency function for photopic vision, [ 34 ] ϕ solar (λ) is the solar irradiance spectrum for air mass 1.5 (AM1.5, corresponding to the sun standing 37° above the horizon), [ 35 ] T (λ) is the measured spectral transmittance, and T is the testing temperature. Compared with the recently reported results of the most studied inorganic VO 2 thermochromic coatings [ 10,36–38 ] and other hydrogel‐based smart windows, [ 17,39–42 ] an unprecedented combination of high T lum (99.05%) and D T solar (33.42%) could be achieved by applying the Gel‐0.8‐NaCl hydrogel (Table S1, Supporting Information). It is notable that the T lum exceeds all the literature data, while the moderate D T solar value can be attributed to the fact that other smart window technologies allow the full regions of the solar irradiation to through and our hydrogels will block infrared spectra.…”
Section: Resultsmentioning
confidence: 79%
“…T lum (380–780 nm), T solar (300–2500 nm) and D T solar could be determined by the following equations: Tlum,solar= ϕlum,solarλTλdλϕlum,solarλdλ ΔTlum,solar=Tlum,solarTTlum,solar20 normalC where ϕ lum (λ) is the standard luminous efficiency function for photopic vision, [ 34 ] ϕ solar (λ) is the solar irradiance spectrum for air mass 1.5 (AM1.5, corresponding to the sun standing 37° above the horizon), [ 35 ] T (λ) is the measured spectral transmittance, and T is the testing temperature. Compared with the recently reported results of the most studied inorganic VO 2 thermochromic coatings [ 10,36–38 ] and other hydrogel‐based smart windows, [ 17,39–42 ] an unprecedented combination of high T lum (99.05%) and D T solar (33.42%) could be achieved by applying the Gel‐0.8‐NaCl hydrogel (Table S1, Supporting Information). It is notable that the T lum exceeds all the literature data, while the moderate D T solar value can be attributed to the fact that other smart window technologies allow the full regions of the solar irradiation to through and our hydrogels will block infrared spectra.…”
Section: Resultsmentioning
confidence: 79%
“…Other thermosensitive materials include poly(N‐vinylcaprolactam), [114] methyl‐ or hydroxypropyl cellulose, [115–118] and polyampholyte hydrogels [119] . It has been reported that a faster thermal response can be achieved in these polymers by incorporating Au nanoparticles or Au nanoparticle clusters (Figures 1d–f) [120] . Owing to the LSPR characteristics of Au nanoparticles and their clusters at visible and near‐infrared frequencies, they are able to absorb and scatter the light with different proportionality according to their geometries [121] .…”
Section: Thermochromic Smart Windowsmentioning
confidence: 99%
“…(e,f) Time‐course change in the window temperatures (e) and indoor temperatures (f) of the bare glass, PNiPAAM‐based smart window, and PNiPAAM‐based smart window containing Au nanoparticle clusters under the irradiation of simulated solar lights. Reproduced with permission [120] . Copyright 2021, American Chemical Society.…”
Section: Thermochromic Smart Windowsmentioning
confidence: 99%
See 2 more Smart Citations